Fatigue behavior of honeycomb sandwich composites under flexural and buckling loading - Topkaya, Tolga; Solmaz, Murat Yavuz (Certex, INCDTP-ICPI, 2016)
This study experimentally investigated the fatigue behaviors of honeycomb-sandwich composites under buckling and three-point bending loads. The ASTM C 365 and ASTM C 393 standards were used as references to prepare test specimens and conduct experiments. The investigation looked at how the cell diameter, core thickness and thickness of the skin material affected the fatigue behavior. It was observed that the most significant parameter affecting fatigue under buckling loads was the cell diameter, and the least significant parameter affecting fatigue under three-point loads was the thickness of the skin material. © 2016 Certex, INCDTP-ICPI.
6th International Conference on Advanced Materials and Systems, ICAMS 2016 -- 20 October 2016 through 22 October 2016 -- Bucharest -- 139798
Keywords: Fatigue; Honeycomb; Sandwich composites